PELATIHAN DAN PENERAPAN TEKNOLOGI TEPAT GUNA BAGI PEMBUAT JAMU TRADISIONAL DI KAWASAN TANJUNG DUREN JAKARTA BARAT - Sobron Lubis; Alifya Askolani Putri; Silvester Lam; Silvi Ariyanti (Universitas Islam Sumatear Utara, 2023)
Health drinks made from spices or known as Jamu, can increase stamina to maintain a healthy body. One of the herbal medicine makers in the Tanjung Duren area is Mrs. Sri Lestari Rahayu, she was active in making herbal medicine during the pandemic. The herbal medicine business that was initiated during Covid 19 is increasing demand from consumers day by day, but not all of these requests can be fulfilled because the processing process is still done manually, especially in the process of cutting raw materials for spices. Based on this, community service activities are carried out. This activity is carried out by providing training on the use of cutting machines and slicing machines. The spice ingredients consist of ginger, lemongrass, turmeric and lemon, each weighing 1 kg. shavings are carried out using a shaved machine with an electric motor drive. After the shaving process, the pulp is separated from the herbal extract using a slicing machine. From the results of the shaving process, it was obtained that the processing time was faster (15 minutes) than before (120 minutes). The results of the spice shavings are very fine. The amount of spices produced can be increased so that consumer demand can be met.